Estudio de ruido laboral, a través de monitoreo por áreas de trabajo para mitigar la exposición de ruido hacia la salud de los trabajadores, de la empresa construcciones Ulloa cia Ltda. Latacunga – Ecuador 2017. diseño de un sistema de insonorización para la mitigación del impacto de ruido laboral. - Jácome Sánchez, María Alejandra (2017)
The companies have the obligation to comply with the Occupational Safety and Health Regulations and the Standard of the Ecuadorian Social Security Institute, within their activities should consider the application of the table of permissible noise decibels so that it does not affect the occupational health. CONSTRUCCIONES ULLOA CIA LTDA, is a company that has the administrative area and production area with work sites where they carry out activities with machinery and tools that generate occupational noise, the noise monitoring that is performed is important since it allows us to determine the Points where the decibels are raised so as to establish a necessary acoustic treatment to the place or process, which is why the construction of soundproofing systems such as acoustic boxes and acoustic barriers with sound-absorbing materials made of polyester polyurethane foam and an insulation High-intensity acoustic vinyl, which will mitigate the noise generated by machinery and workmanship in the company, in addition to the application of Personal Acoustic Protection Equipment 3M ™ EAR ™ Ultrafit ™ Earplugs , 32 dB, Corded, 50 Per Pack, UF-01-000, which complies with the different structural conditions that mitigates the noise levels that are generated in the company.